Problems of the History and Culture of Baktria in Light of Archaeological Excavations in Central Asia - Litvinskii, Boris A. (Anabasis. Studia Classica et Orientalia, 2010)
The Achaemenid conquest of Baktria and its organization into a satrapy resulted in the production of Achaemenid art and other forms of material culture in the region. The Greeks whom the Achaemenids had deported from Ionia appeared in Baktria while it was still a satrapy. It was from this point that Greek culture rapidly spread in all spheres of everyday and spiritual life, stimulated as it were by two essential factors: a high standard of technology, especially in the realm of construction, and the interaction of Greek and Avestan mythology. The processes of adaptation, adoption and assimilation of Achaemenid and Greek culture began in the Achaemenid period and accelerated under the Seleukids and Graeco-Baktrians. Ai Khanoum and the Temple of the Oxos serve as excellent examples. The formation of an eastern brand of Hellenistic architectural and artistic koine over a vast region of the Orient is seen in the development of fine arts and the subsequent “golden age” of art schools based on a common Achaemenid-Baktrian heritage. It is out of this cultural synthesis of Greeks and Baktrians that the phenomenon that we term “Graeco-Baktrian” emerged to dominate all spheres of everyday life. The study of the art from the Temple of the Oxos allows us to conclude that it is unquestionably a Baktrian inspired temple, whose adherents included both ordinary and elite Baktrians. In addition, a significant portion of the art assembled in the sanctuary’s repositories originated in Iran, Asia Minor, and the Hellenistic Mediterranean. In the Hellenistic era large Baktrian city centers, including those with temples, like the Temple of the Oxos, served as “melting-pots,” where art, technology and ideas fused to create a new intense historical and cultural synthesis, thereby becoming the Baktrian school of Kushan art. This in its turn co-existed with the school of Indo-Gandhara art. Greek culture had a significant impact on the evolution of culture in Central Asia, including architecture, toreutics, coroplastics, religious and mythological themes and musical instruments among many others. The degree of Hellenistic and Roman influence fueled by the popularity of Gandhara art in Central Asia increased during the Kushan period. In addition, we also see at this time the influence of Parthian and Palmyran art. By the beginning of the first century A.D., all these elements became so closely and creatively intertwined that it is possible to discuss a fully matured “Baktrian art.” In this context, the complexes of Khalchayan and Tillya-tepe are of paramount importance. Certain elements of Hellenistic spiritual and material culture survived in Baktria and even in the whole of Central Asia throughout the period of the Kushans and the subsequent Hephtalite Empire until the Arab conquest, while architectural influence remained intact much longer. Antiquity not only formed the basis of Western European civilization but it also formed the basis of a Central Asian civilization that drew heavily from its Hellenistic (and Hellenistic-Roman) roots.